Ventilação natural em escolas na cidade de Campina Grande: a influência da velocidade do ar na percepção e sensação de conforto térmico do usuário - Macedo, Pollyanna Padre de (2021)
Natural ventilation is a parameter that should be taken into consideration in architectural projects, as it helps to reduce undesirable heat gains, cooling the environment and providing a greater possibility of being perceived as pleasant for the development of activities. Therefore, the relationship between ventilation and the quality of the built environment is a relevant factor for school buildings, where thermal comfort must be promoted in order to provide an adequate space for teaching, enabling greater productivity and quality of work. However, comfort is not only related to the physical environment, but also to the subjective and individual issues of the user, such as the perception and sensation of thermal comfort in the space. So, through questionnaire, on-site measurements, observation and data analysis, the objective of this research was to identify the limits of air velocity regarding the sensation and perception of thermal comfort of students from public high schools in Campina Grande, Paraíba; when confronting the air velocity limits stipulated by the literature with the velocitiesidentified in the research, in order to have a better understanding of the relationship between the intensity of air movement and the subjective aspects of individuals in the semiarid climate. The experiment included seven schools, which, in the winter, a sample of 569 participants was obtained, with an average air temperatures from 22,44 to 26,28 °C and an average air velocity from 0,15 to 0,34 m/s; and in the summer period, the sample was 646 participants, with an temperatures from 25,91 to 30,78 °C and average velocity from 0,23 to 0,51 m/s. Regarding the thermal sensation, in the winter, most students (35,85%) declared that they were slightly cold; and similarly, in the summer, 33,44% said they felt very hot. Nevertheless, 87% of students indicated the thermal environment as acceptable, and 33,57% as comfortable in the winter. In the summer, however, 47,83% said it was thermally acceptable, and only 13,62%, comfortable. Furthermore, the acceptability of wind velocity and the preference for more wind velocity was 84,7% and 45,16%, respectively, for the winter; and 51,54% and 81,89%, for the summer. On the other hand, as for the statistical tests of air velocity, there was significance only regarding the thermal preference in winter, indicating that the increase of 0,1m/s in the air velocity raises the chances in 37,6% of the occupant preferring the cooler thermal environment. In the summer, the increase in air velocity of 0,1m/s improves the student's chances of indicating cooler thermal sensations by 10,81%; as well as, it can also reduce the chances of the user to prefer the cooler thermal environment by 7,74%. Finally, it appears that there is compliance with the air velocity limits stipulated in the literature in general, since air velocity above 0,50 m/s were considered acceptable in the winter; and above 0,80 m/s, in the summer; concluding that greater air velocity intensity in naturally ventilated school environments can be accepted by the students.